(3GdoYOI hGNJUGQg GdoYeOIs - (3YKeGf Hf Ydj Hf YeQh GdNRQLj GdSQbhSj GdUbdj , CHh YeQhs
(3ChdgG (B:s
(3gPG cJGH GNJUQJ ajg GdYeOI dCHj Ydj MSf Hf QTjb bOeJ ajg cd TF Edi Tcdg, hcd eYfi Edi eKdg, hcd aQY Edi CUdg hfbUJ eG ajg ef MTh hESgGH s
(3BNQgG (B:s
(3hbY ajgeG LqdI ef GdeJbOejf, hCdJeS dge ajgeG GdYPQ aef GdEMGdI bhd GHf ebHd cja jchf fSL OGhO ef YgO YGO heY PG aGdEMGdI HGbjI s
(3GdYeOI dGHf QTjb GdbjQhGfs
(3GdfSNI HgG MhGTs
(3ChQGbg GdChdi HNW eZGjQ eJCNQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs